Sociological Analysis of Islamic Law on The Implementation of the Jo Kawin Bocah Program in Reducing Early Marriage Rates (Case Study on the PKK Team of Temanggung Regency) - Rahmadani, Luqiya Suci; Ibrahim, Malik; Muhammad, Hanifah Salma (Jurnal Syariah dan Hukum Komparatif, 2024)
The "Jo Kawin Bocah" program aims to prevent early marriages in Central Java, particularly in Temanggung Regency, where 414 cases were recorded in 2022. Implemented by the PKK Movement Team, the program focuses on educating communities to reduce early marriage rates. This research analyzes its implementation in Temanggung Regency in 2023 using a sociological approach to Islamic law and descriptive analysis. The findings reveal two main points. First, the PKK Movement Team enhances the program through collaboration with the government, communities, institutions like GenRe (Planned Generation), and mass media for effective dissemination. Second, based on Atho' Mudzhar's sociological theory of Islamic law, factors such as religious practices, social structures, interactions, and support from community organizations significantly influence the program's outcomes. By fostering awareness and community involvement, the program has successfully shifted perceptions and reduced early marriage practices in Temanggung, demonstrating its potential as a model for other regions.